Risk Communication and public perception of technological hazards. First Volume - Virginia Recchia (Fondazione Eni Enrico Mattei (FEEM), 1999)
Research on risk communication relates basic risk perception studies to the formulation of policies, the currently evolving legislation dealing with hazards, the key issues of public involvement, the risk and environmental management. Risk communication is a relatively new field based on a sociological approach. The discipline comes from risk perception studies (psychological approach), which try to investigate how the public is influenced by certain variables in perceiving risk as "acceptable" or not. Risk communication involves some aspects of risk analysis methodology, since it results that also the technical analysis is influenced by the co-operation between the actors involved. The research project includes two aspects: a theoretic approach on risk communication (Part one) and a case study (Part two). The analysed case is relative to a movement plant of petroleum products. The method used for the analysis foresees a review of the main findings about risk perception and communication: mostly about the factors, which influence the public perception of risk. On the basis of these factors a content analysis of technical documents, of local newspapers, and of public documents and reports was carried out. The main objective of this project is to establish recommendations and proposals for a communication strategy aimed at consensual decision making. This strategy would act on awareness and/or equilibrium in risk perception, as a condition necessary to achieve consensus.
Keywords: A14; D74; L15; Q2; Q3; 330; Risk; acceptability; perception; environment; consensus; actors; stakeholders; hazard; public; local community; variable; communication; environmental communication; risk perception; risk analysis; risk management; consensus building; technological hazards; stakeholder analysis; risk acceptability; public involvement; siting/localisation of hazardous facilities; chronic risk; acute risk; toxic emissions; emergency plan; dilemmas; Risikomanagement; Technikbewertung; Wahrnehmung; Theorie